Effectiveness and tolerability of chlormethine gel for the management of mycosis fungoides: a multicenter real-life evaluation - Alberti-Violetti, Silvia; Ardigò, Marco; Massone, Cesare; Pileri, Alessandro; Sala, Raffaella; Teoli, Miriam; Grandi, Vieri; Quaglino, Pietro; Pimpinelli, Nicola; Berti, Emilio (Frontiers in Oncology, 2024)
Background Topical chlormethine (CL) is recommended as a first-line treatment for early-stage mycosis fungoides (MF) and in 2017, the European Medicines Agency approved the CL gel formulation to treat adult patients. More recently, to increase patient compliance and adherence, clinicians have developed flexible protocols that allow the concomitant use of CL gel with topical corticosteroids in daily practice regimens. Therefore, sharing real-life data on CL gel use and side effects management may help improve the use of this agent. Objectives To expand knowledge about the actual use of CL gel in patients with MF, the present study assessed the improvement of MF skin lesions after CL gel treatment and provided information on the management of cutaneous adverse events (AEs) in a real-life setting. Methods This was an Italian retrospective study conducted among six dermatology referral centers. Patients ≥18 years affected by MF and in treatment with CL gel (160 µ/g), alone or in combination according to routine clinical practice, between December 2019 and December 2021 were considered. The study’s primary aim was to evaluate the effectiveness of CL gel in terms of overall response rate (ORR) after 3 months of treatment. Results A total of 79 patients (61% male) with different stages of MF (84% early stage) were included. CL gel was prescribed mainly in association with topical corticosteroids (66% of patients). ORR after 3 months of treatment was 42%, with no differences between early- and advanced-stage MF. Response rates improved over time up to 97% after 18 months of treatment. Overall, 66 AEs were reported in 67% of patients; most were hyperpigmentation (45%) and irritant contact dermatitis (37%). Six AEs led to treatment discontinuation, and five out of six (83%) patients who reported these events resumed treatment after interruption. No AEs were classified as severe. Conclusions Our observations support the use of CL gel in patients with early- and advanced-stage MF, making it a valuable treatment option.